Dobór systemu rachunku kosztów dla specyfiki promocji - Targowicz, Marta (Issue Of Selecting a Cost Account System in Promotional Activities, 2007)
Keeping the promotional cost account may be done in two ways: adjusting company's cost records for the purposes of distinguishing promotional costs (reporting system), establishing an off-the-record costs account which takes into consideration the specifics of a promotion system (for the purposes of cost management). Analysis of possible solutions to the selection of a promotional cost account system should be carried out depending on the type of activity and foremost on the scope of promotional activities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 486-493